Pembentukan Karakter Insan Kamil Melalui Program Halaqah Tahfidzul Qur’an di SMPIT Permata Hati Merangin Jambi - Bukhori, Susianto Al (Edification Journal : Pendidikan Agama Islam, 2022)
Insan Kamil is an ideal human being who has commendable character and character in accordance with Islamic teachings. However, to achieve this requires a method or method. One of the achievements is through the halaqah tahfizhul qur'an program. That's why SMPIT Permata Hati Merangin as an Islamic educational institution includes the Halaqah Tahfizhul Qur'an program as the main subject at school. Because by constantly interacting with the Qur'an, both reading and memorizing it, students will feel that they are always under the supervision of Allah SWT. The purpose of this research is to find out Halaqah Tahfzhul Qur'an Program and character formation of human. This form of research uses a qualitative approach. The results of the study that the tahfiz program consists of Tahsin and memorization and character building which can be in the form of honesty, discipline, responsibility, istiqomah (consistent), optimistic and polite